Ambang Batas Reasuransi Non-Proporsional Menggunakan Tail Value-At-Risk (TVaR) dari Distribusi Peluang Campuran - Eurico, David; Afifatul Ayu Astiani; I Kadek Darma Arnawa; Bagas Caesar Suherlan; Utriweni (Jurnal Statistika dan Aplikasinya, 2023)
One of the tasks of banking institutions is to channel funds to the public through loan products. Banking institutions transfer the risk of non-performing loans to insurance companies and then partially reinsured to reinsurers. The purpose of this study is to determine the non-proportional reinsurance threshold based on the risk of loss of the 20% largest loan principal, using the Tail Value-at-Risk (TVaR) method. The threshold value will be estimated using a sample of 5,000 loans principal. The loan characteristics can be described by a Mixture Gamma Distribution consisting of components with different weights and parameters. The weights and parameters are 19% from the Gamma distribution with parameters α = 2.45 and β = 0.04, 34.5% from Gamma with parameters α = 8.29 and β = 0.07, and 46.5% from Gamma with parameters α = 30 and β = 0.13. Analysis using TVaR produces a threshold value of 274.9 million rupiah. In real cases, if the claim value exceeds 274.9 million rupiah. The insurance company will bear a value of 274.9 million rupiah and the reinsurer will bear the difference in the size of the claim against the threshold limit.